2019
DOI: 10.1002/adtp.201900129
|View full text |Cite
|
Sign up to set email alerts
|

Highly Biocompatible Functionalized Layer‐by‐Layer Ginger Lipid Nano Vectors Targeting P‐Selectin for Delivery of Doxorubicin to Treat Colon Cancer

Abstract: A biocompatible natural nanoparticle drug delivery system that has specific cancer-targeting function holds vast promise for cancer therapy. Here, a fucoidan/poly-lysine-functionalized layer-by-layer ginger-derived lipid vector (LbL-GDLV) is designed to target P-selectin and deliver a loaded drug into vascularized colon cancer. LbL-GDLVs selectively bound to P-selectin, and the degradation of the fucoidan result in rapid attachment of the cancer cell and internalization of the remaining positively charged poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…10 Ginger PDNP-derived nano vectors have also been employed for the targeted delivery of cargos to cancer cells in vivo, via coencapsulating cancer-targeting ligands such as folic acid (FA), highlighting the potential of ginger PDNPs as a cost-effective nanocarrier. 11,12 MicroRNAs (miRNAs) are small, endogenously derived 18−25 nt RNAs which regulate target mRNAs by translational repression and/or transcript degradation. Three independent studies have shown the presence of miRNAs in ginger PDNPs with potential therapeutic benefits.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Ginger PDNP-derived nano vectors have also been employed for the targeted delivery of cargos to cancer cells in vivo, via coencapsulating cancer-targeting ligands such as folic acid (FA), highlighting the potential of ginger PDNPs as a cost-effective nanocarrier. 11,12 MicroRNAs (miRNAs) are small, endogenously derived 18−25 nt RNAs which regulate target mRNAs by translational repression and/or transcript degradation. Three independent studies have shown the presence of miRNAs in ginger PDNPs with potential therapeutic benefits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly, ginger PDNP-derived lipids were used as nanocarriers for oral delivery of siRNA against divalent metal-ion transporter (Dmt1) to treat hereditary hemochromatosis . Ginger PDNP-derived nano vectors have also been employed for the targeted delivery of cargos to cancer cells in vivo , via co-encapsulating cancer-targeting ligands such as folic acid (FA), highlighting the potential of ginger PDNPs as a cost-effective nanocarrier. , …”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived natural NPs are used to overcome off-target cytotoxicity and high cost of mass production of traditional NPs. Nanocarriers derived from edible plants, such as ginger, grapefruit, broccoli, and lemon, can be used for drug delivery ( Wang et al, 2013 ; Zhang et al, 2016a , b ; Yang et al, 2018 ; Zhang M. et al, 2019 ). These nanocarriers have exosomal-like traits and can be applied in exosome-based drug delivery systems.…”
Section: Applications Of Oral Anti-crc Nanotherapeuticsmentioning
confidence: 99%
“…P-selectin is a membrane glycoprotein expressed on vascular endothelial cells in most tissues, and is a member of the selectin family that mediates cell rolling and platelet adhesion. It plays an important role in the accumulation of white blood cells towards the damaged site in the early stage of inflammation [ 45 48 ]. Notably, elevated P-selectin expression was found in inflammatory sites of the ulcerative colon but not healthy tissues in humans and mice, suggesting that P-selectin may be a specific target for delivery of nanomedicine to the colon in the treatment of UC.…”
Section: Introductionmentioning
confidence: 99%